Care vs Survival: A Difficult Choice During the Crisis. Causes And Implications of the Statuto Cinema Fire (1983) (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
Taking care of a film audience means, above all, keeping it safe and protecting its health. This duty has not always been accomplished. In the history of the Italian cinema exhibition, sometimes specta- tor safety conflicted with the financial survival of movie theatres.From the late 1970s, Italy’s exhibition sector suffered from a severe economic crisis due to diminish- ing cinema attendance. While the exhibitors union AGIS tried to ease official security regulations, many theatres gave up caring for their audience in order to survive. The tension culminated most visibly in a tragic fire disaster in Turin. On 13 February 1983 the Statuto Cinema burned down, result- ing in 64 deaths. This case exemplifies the challenging trade-off between adapting modern security standards and maintaining the economic viability of movie theatres.The article analyses the Statuto disaster itself and contextualises the incident within the broader contemporary trade discussion about safety concerns. Light is shed on the negotiations between the safety authorities and the exhibitors union prior to 1983, and the difficult choice between investing or surviving that concerned many exhibitors. Drawing on archival material from the AGIS archive, the article traces how cinema managers experienced this historical period of change and assessed risk for film audiences in the late 1970s and early 1980s.
Keywords: Safety; Business; Cinema Exhibition; Psychology; Risk